Critical success factors of listed electronics companies that were negatively correlated to the economic crisis in 1998. - Chua, Cindy Jin Bei. (2008)
Our project investigates the critical success factors of selected listed electronics companies in Singapore that experienced an improvement in net profit (or a reduction in net loss) and earnings per share in 1998, despite the dismay economy due to the regional economic crisis.